If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -17 = 10x + 17 Reorder the terms: -17 + 11x = 10x + 17 Reorder the terms: -17 + 11x = 17 + 10x Solving -17 + 11x = 17 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -17 + 11x + -10x = 17 + 10x + -10x Combine like terms: 11x + -10x = 1x -17 + 1x = 17 + 10x + -10x Combine like terms: 10x + -10x = 0 -17 + 1x = 17 + 0 -17 + 1x = 17 Add '17' to each side of the equation. -17 + 17 + 1x = 17 + 17 Combine like terms: -17 + 17 = 0 0 + 1x = 17 + 17 1x = 17 + 17 Combine like terms: 17 + 17 = 34 1x = 34 Divide each side by '1'. x = 34 Simplifying x = 34
| 3.8+10m=7.31 | | x/7-x/14-x=8 | | 6(b+1)=3 | | 5x+2y+x+y=63 | | 3x-4=7x-44 | | 2y^2+27y-45=0 | | (x^2-x+1)-(2x^2-1)=0 | | 3x-72=-6x+126 | | 1.5x+1.3x=-8 | | 5y+1-y=10+3y+10 | | m+2n=p*n | | f(x)=(x-6) | | 21=4x+3 | | 3.25+0.50x=4.75+0.75x | | f(-x)=4x^2+3x+6 | | 19z=14y-y-3z | | -156=-8+4(-7+6a) | | 6y^2+19y+13=0 | | 3n+g+4n=2 | | (4y-4)+9=29 | | 2x-88=122-8x | | 28=18+x-20 | | (-3+3y)+3=3y | | 13+9x+24=x-3 | | 3(-10t-3)=75 | | y=3.8-2x | | 105-14=s | | 11+4a=1+a+-7a | | -7x-27=8-x-19 | | (3x)+(x-6)=90 | | 4z+z=40-10 | | 2x^2-19x-98=0 |